2020
DOI: 10.1021/acs.nanolett.0c01774
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carbonate-Based Additives on the Electrochemical Performance of Si NW Anodes Cycled in an Ionic Liquid Electrolyte

Abstract: Addition of electrolyte additives (ethylene or vinylene carbonate) is shown to dramatically improve the cycling stability and capacity retention (1600 mAh g −1 ) of Si nanowires (NWs) in a safe ionic liquid (IL) electrolyte (0.1LiTFSI-0.6PYR 13 FSI-0.3PYR 13 TFSI). We show, using postmortem SEM and TEM, a distinct difference in morphologies of the active material after cycling in the presence or absence of the additives. The difference in performance is shown by postmortem XPS analysis to arise from a notable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 83 publications
0
19
0
Order By: Relevance
“…[53,54] Also, a peak is observed at 400.1 eV in the N1s spectrum of the H-LNMO electrode after the 1st charge of the H-LNMO cell with RTIL electrolyte, further confirming that the FSIanion contributes to the formation of the CEI layer ( Figure S3, Supporting Information). [51,54,55] The integrated area ratio of the carbon-oxygen bonds and TM-O decreases for the H-LNMO electrode cycled with LP30 electrolyte, consistent with the exposure of pristine H-LNMO surface observed in the ex situ TEM results. Therefore, it is speculated that the vulnerable CEI layer was attacked by byproducts during electrolyte decomposition, degrading into a non-uniform CEI layer.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…[53,54] Also, a peak is observed at 400.1 eV in the N1s spectrum of the H-LNMO electrode after the 1st charge of the H-LNMO cell with RTIL electrolyte, further confirming that the FSIanion contributes to the formation of the CEI layer ( Figure S3, Supporting Information). [51,54,55] The integrated area ratio of the carbon-oxygen bonds and TM-O decreases for the H-LNMO electrode cycled with LP30 electrolyte, consistent with the exposure of pristine H-LNMO surface observed in the ex situ TEM results. Therefore, it is speculated that the vulnerable CEI layer was attacked by byproducts during electrolyte decomposition, degrading into a non-uniform CEI layer.…”
Section: Resultsmentioning
confidence: 63%
“…Instead of carbon-related species, a significant amount of SO 2 moiety (532.9 eV) is present in the O 1s spectra, derived from the decomposition of FSI – anions (Figure d). , The S2p spectrum of the H-LNMO electrode after the first charge also supports the observation of SO 2 at 169.3 and 170.5 eV for 2p 3/2 and 2p 1/2 , respectively (Figure S5). , The SO 2 moiety is considered to be an effective functional group to improve the surface stability of cathodes because it only allows Li + migration by partial negative charge of oxygen atoms while inhibiting the electron transfer at the interface between the electrode and the electrolyte, thus suppressing electrolyte decomposition during cycling. , Also, a peak is observed at 400.1 eV in the N 1s spectrum of the H-LNMO electrode after the first charge of the H-LNMO cell with the RTIL electrolyte, further confirming that the FSI – anion contributes to the formation of the CEI layer (Figure S5). ,, …”
Section: Results and Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The quantitative analyses of Si components are 0, 1.05, 1.40, and 1.61% in Table S3. The high-resolution Si 2p spectrum in Figure b showed a single peak located at binding energies of 102 ± 0.4 eV, which is assigned to the Si–O bond. The surface species of activated carbon are determined with FTIR (Figure c and Figure S3). Compared with OAC, the characteristic peaks of SACs at 869, 1112, and 2916 cm –1 , which are attributed to Si–O–C, Si–O–Si, and −CH 2 , , respectively, gradually increase corresponding to the increasing of the loaded siloxane.…”
Section: Resultsmentioning
confidence: 99%
“…When the ionic liquid's anion is modified with ferrocene, self-discharge is fully suppressed due to the deposition of a film on the electrode. Stokes et al [209] reported the positive effects of the addition of SEI forming additives (EC and VC) on the performance of Si NWs anodes in a 0.1LiTFSI-0.6PYR 13 FSI-0.3PYR 13 TFSI IL electrolyte (Figure 11f1). The base IL electrolyte used combines FSI − and TFSI − ions to access a combination of properties such as wide electrochemical window, good chemical and thermal stability, flame retardancy, and negligible vapor pressures.…”
Section: Modifying Surface and Interfacementioning
confidence: 99%